The Influence Of Western Culture In Elinore's Inner Conflict In Sense And Sensibility Psychoanalytic Approach - Nur Utami, Lia; , Dr. Phil. Dewi Candraningrum, S. Pd, M. Ed (2016)
The major problem of this study is to explain how the major character with her inner conflict and how she solve her problem at that moment. The major problem of major character based on structural elements and to analyze the novel based on psychoanalytic theory. In analyzing novel Sense and Sensibility by Jane Austen, the researcher uses qualitative method and psychoanalytic theory. The object of the study is Jane Austen's Novel entitled "Sense and Sensibility" published 1811 by Thomas Eagerton of the Military Library. The primary data source is the novel "Sense and Sensibility" it and the secondary data source is the other sources related to the analysis such as the author biography and books of literary theory. In this research the researcher also use psychological books, especially psychological book which discussing about psychoanalytic theory by Sigmund Freud. The method of data collection is library research. The technique of data analysis is descriptive analysis. The study shows that the problem happened by the major character Elinor Dashwood cause of her mental condition that is inner conflict. Inner conflict makes her suffered because in major character's heart there was a controversy between good and bad action and feeling.